TAX AVOIDANCE IN REVIEW BY BUSINESS STRATEGY, COMPANY CHARACTERISTICS, AND GOOD CORPORATE GOVERNANCE - Yunus Harjito (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
This study aims to analyze the effect of business strategy, company characteristics (liquidity, profitability, leverage, company size) and corporate governance on tax avoidance. The tax avoidance variable is represented by the cash effective tax rate (CETR). This study uses a sample of 52 companies which meet the criteria i.e. listed on the IDX in 2015-2019 and listed on the Corporate Governance Perception Index ranking. The data was analyzed using IBM SPSS Statistics version 23 software. The results show that business strategy, liquidity, company size, and corporate governance have an effect on tax avoidance. Meanwhile, profitability and leverage have no effect on tax avoidance.